TINGKAT KESUKAAN PANELIS TERHADAP MINUMAN SARI BUAH SALAK DENGAN MENAMBAHKAN MADU KELENGKENG MELALUI UJI HEDONIK - Arya Kariawan, Kadek Dwi; Pastini, Ni Wayan (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2023)
Salak fruit juice mixed with longan honey is a nonalcoholic drink made from zalacca juice and longan honey. The maker of this drink begins with squeezing and boiling the salak fruit which is then filtered and does not undergo a fermentation process. This drink can be drunk immediately because it is refreshing. This study aims to determine the level of panelist’s preference for salak fruit juice by adding longan honey through a hedonic test. This study used a quantitative descriptive technique to determine the level of panelists' preference for salak fruit juice by adding longan honey. The results showed that the indicator of salak fruit fuice drink by adding longan honey, color got 3.93 (likes), aroma got 4.0 (likes), sweetness got 4.06 (likes), acidity get a result of 3.46 (likes) and the overall average obtained was 3.86 which stated that the panelists (liked) the salak fruit juice drink by adding longan honey. It is hoped that the results of this study can be marketed because the results of the hedonic test show good results as a product that is marketable.